A Study to Compare the Stress Patterns in the Edenulous - Shobha Rodrigues1, Thilak Shetty2, Umesh Pai3, Sharon Saldanha3, Mahesh M3, Puneeth Hegde3, Mandakin (Institute of Medico-legal Publications Pvt Ltd, 2020)
Purpose: Occupational exposure to blood borne pathogens with needle stick or other sharp tool injuries is a serious but preventable problem. this study will be conducted to investigate the incidence of Needle stick injury (NSI) among the Dental health care providers (DHCP) of Manipal College of Dental Sciences, Mangalore.Method: The NSI incidence, demographics, contributing factors, and follow up following NSI report were reviewed.Results : Six, eleven , seventeen and nineteen needle stick injuries were reported in 2010, 2011, 2012 and 2013 respectively . Most injuries were experienced by students and least by the Faculty.Conclusion: Based on the results and within the limitations of this surveillance study it is concluded that occupational exposures can be reduced and reporting of all exposures is vital. The institution of appropriate PEP, psychological support and counselling of affected HCWs and stringent follow-up are all needed to reduce the burden of occupationally acquired infections in HCWs